2016
DOI: 10.1007/s10653-016-9796-2
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of metal bioaccessibility in vegetables to improve human exposure assessments: field study of soil–plant–atmosphere transfers in urban areas, South China

Abstract: The quality of cultivated consumed vegetables in relation to environmental pollution is a crucial issue for urban and peri-urban areas, which host the majority of people at the global scale. In order to evaluate the fate of metals in urban soil-plant-atmosphere systems and their consequences on human exposure, a field study was conducted at two different sites near a waste incinerator (site A) and a highway (site B). Metal concentrations were measured in the soil, settled atmospheric particulate matter (PM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(41 citation statements)
references
References 70 publications
1
40
0
Order By: Relevance
“…Additionally, the atmospheric particulate material that sets down on plants’ surfaces can contaminate them. Xiong et al [22] found that vegetables are high in lead and cadmium concentrations originating from air pollution. Industrial particulate contributes to 25% to 40% of total PTEs concentration, which deposits on plants’ leaves and is absorbed through their vascular system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the atmospheric particulate material that sets down on plants’ surfaces can contaminate them. Xiong et al [22] found that vegetables are high in lead and cadmium concentrations originating from air pollution. Industrial particulate contributes to 25% to 40% of total PTEs concentration, which deposits on plants’ leaves and is absorbed through their vascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Industrial particulate contributes to 25% to 40% of total PTEs concentration, which deposits on plants’ leaves and is absorbed through their vascular system. Waste incineration and traffic flow contribute to particulate material emission as well [22]. The diet is considered a relevant source for some toxicants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Long time exposure to arsenic results in its accumulation in muscles, nails, hair, and skin which leads to different complications and disorders. 5,6 The complications of arsenic poisoning about the heart will cause prolonged and severe abnormal cardiac repolarization, resulting in a fatal arrhythmia. 7 It will also cause coronary heart disease and peripheral vascular disease in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric deposition (As, Pb, Cr, Hg, Cu, Cd and U) 4. Soil heavy metal(loid)s pollution, food-chain contamination and human health Consumption of food contaminated with heavy metal(loid)s is considered to be the major pathway (N 90%) of human exposure compared to dermal contact or inhalation (Mombo et al, 2015;Xiong et al, 2016b). Soil is the direct path way for the contamination of heavy metal(loid)s in vegetables and crops via root uptake .…”
Section: Anthropogenic Sourcesmentioning
confidence: 99%